The impact of cricoid pressure on oesophagus position and compressibility in Malaysian patients: A prevalence study / Aaron Wilson - Aaron, Wilson (2019)
Background Cricoid pressure (CP) is an airway manoeuvre used during rapid sequence induction to reduce the risk of pulmonary aspiration. Classically it was thought that CP was effective for this as it compressed onto the oesophagus located centrally. However, anatomical studies involving CP showed various relative oesophagus positions with variable degrees of compressibility, and ultrasound is a non-invasive tool that could be used to assess these parameters. Purpose: To determine the sonographic prevalence of relative position of oesophagus to cricoid cartilage in patients undergoing general anaesthesia; and to assess the qualitative impact of CP on change of oesophagus position and its compressibility. Methods A prospective, cross-sectional study was performed on patients would undergo general anaesthesia for elective surgery in single tertiary centre in Malaysia. Written consent obtained from all eligible patients. Prior to induction of general anaesthesia, baseline ultrasound scan of the neck to assess the position of oesophagus relative to cricoid cartilage was done and designated as either: central, partially lateral, or completely lateral. Scan was repeated post general anaesthesia and pre CP. Then CP force of 30N was applied on cricoid cartilage. Patient’s sonogram was assigned to one of three groups: directly behind the trachea (“central”), partially behind trachea (“partial”), or completely lateral to the trachea (“lateral”). Oesophagus was assumed “central” (and iii compressible) if scan did not detect oesophagus; “partial”, if the entire tubular structure of the oesophagus located behind cricoid cartilage was not visualised (lateral borders of cricoid cartilage and the oesophagus overlapped); and “central”, if there lateral border of the two structures overlapped. The position and compressibility of oesophagus were recorded. Two investigators with fixed roles were involved in obtaining the data, whereby one applied CP and the other performed the ultrasound scan of the neck. Chi square test, McNemar or Fisher exact was performed for statistical analysis (α = 0.05). Results There were 50 patients recruited. Results pre vs post general anaesthesia were as follow: 44% (vs 34%) patients with central oesophagus, 42% (vs 44%) were partial and 14% (vs 22%) lateral. The effect of general anaesthesia on oesophagus placement was significant (p = 0.046). There is no change in oesophagus position pre and post CP. There was higher prevalence (54%) of oesophagus occlusion with CP in the central and partial groups (p <0.001). No oesophagus occlusion seen in lateral group. Conclusions There was more non-centrally located oesophagus compared to central oesophagus. Anaesthesia effect has an association with further displacing the oesophagus. Oesophagus occlusion was less likely if it is deviated from cricoid cartilage.